Morphological and structural characterization of fly ash powders - Peña-Rodríguez, Gabriel; Ortega-Triana, Luis René (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
Morphological and structural characterization of fly ash powder's reports are obtained from coal  combustion supplied by the thermal - electrical plant Termotasajero S.A. The morphological study consisted in the superficial analysis, using Scanning electron microscopy (SEM). The basic chemical composition was found using X ray energy dispersion spectrums (EDX - SEM) whereas structural characterization was developed by X-ray diffraction (XRD). The software Image tool V. 3.0. was used for the particle size distribution. The results obtained show that the fly ash powders are composed mostly by spherical particles as well as unburned particles adhered to the particles, with average particle size of order micrometers. The structural study, using XRD, reports the main crystalline phases of mullite, quartz and hematite. Our results will allow us to evaluate the Thermal - electrical Plant Termotasajero's coal combustion processes, as well as another uses and applications of those ashes.